Factors Influencing e-Government Adoption (A Case Study of Information System Adoption in PPATK) (Faktor-faktor yang Memengaruhi Adopsi e-Government (Studi Kasus Adopsi Sistem Informasi di PPATK)) - Syarifah Hanum; Rabiah Al Adawiyah; Dana Indra Sensuse; Jonathan Sofian Lusa; Assaf Arief; Pudy Prima (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2020)
Information Communication Technology (ICT) has encouraged e-government implementation to improve government institution performance in society, business and fellow government institutions. Many Information Systems (IS) are created and used, but not all of them are successful. This is contrary to the expectations that were mentioned earlier. Therefore, it is necessary to conduct research to identify factors that influence e- government adoption. This paper presents a case study of information system adoption in a government institution. The study was conducted using TOE methods. Data were collected using qualitative method and subsequently processed using Qualitative Data Analysis tools. Results indicated that all factors analyzed in TOE framework influenced IS adoption. However, not all factors were properly conducted. Therefore, they need to be developed to address difficulties in IS adoption so it will meet the e-government implementation expectation.